Status of Museum Libraries in Delhi: An Overview - Simerjit, Kaur (Zenodo, 2019)
Museums are memory institutions which preserve cultural and historical memories of a society in the form of tangible and intangible cultural heritage. Museums are the institutions where citizens of a country can realize both the glory as well as struggle of development of a country. The museums pass on the cultural heritage to future generations through collection of objects. Educational and research values of these cultural institutions depend on what services they are providing to its users. The museum library being special library in nature provides support to its parent museum to carry on different activities by furnishing relevant updated information and in this way explores its potential use. The paper presents the historical development of museums and its libraries in Delhi. It defines the museum and museum library. The aims and objectives of museum libraries are discussed in detail. The status of museum libraries in terms of collection and services has been discussed.